Do School Resource Officers Really Refer Juveniles to the Juvenile Justice System for Less Serious Offenses?. (February 2018) - May, David C.; Barranco, Raymond; Stokes, Ethan; Robertson, Angela A.; Haynes, Stacy H.
In this article, we use 3 years of youth court data from a southeastern state to examine whether referrals that originated from school resource officers (SROs) involve greater proportions of less serious offenses than referrals from other sources. Referrals from SROs during the 3-year period were similar to referrals by law enforcement outside of school for status and serious offenses. SROs were less likely than law enforcement officers outside of school to refer juveniles for minor offenses during the 3-year period. Our findings suggest that schools, not solely police in schools, make a large contribution to the number of juveniles referred to the juvenile justice system for less serious offenses. Implications for policy and future research are also discussed.